2011
DOI: 10.1590/s0102-86502011000100002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optical density of bone defects filled with calcium phosphate cement and bioactive glass in rats

Abstract: Purpose: To evaluate new bone formation, by the analysis of optical density, in rat femoral defects filled with calcium phosphate cement (CPC) and bioactive glass (BG). Methods: Twenty-one rats were divided into three groups, Group I (CPC), Group II (BG), and Group III (control), and assessed after 7, 15, and 30 days. Three bone cavities were made in the left femur and filled with CPC, BG, and no material (control). Digital images were obtained and the results were subjected to statistical analysis of variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The histological analyses also demonstrated that there was no inflammatory response or necrosis in any of the animals, and this is concordant with studies that aimed to assess the biocompatibility of α-TCP cement 39 , 40 . Another possible explanation for the absence of inflammation or bone necrosis is that saline solution was used to constantly irrigate the surgical field while the defects were being created, and that both the cement and the surgical materials used in all the procedures had been sterilized.…”
Section: Discussionsupporting
confidence: 85%
“…The histological analyses also demonstrated that there was no inflammatory response or necrosis in any of the animals, and this is concordant with studies that aimed to assess the biocompatibility of α-TCP cement 39 , 40 . Another possible explanation for the absence of inflammation or bone necrosis is that saline solution was used to constantly irrigate the surgical field while the defects were being created, and that both the cement and the surgical materials used in all the procedures had been sterilized.…”
Section: Discussionsupporting
confidence: 85%
“…Studies have proven that combining PRP with biomaterials optimizes and accelerates the bone tissue regeneration process (38) . The histological analyses also demonstrated that there was no inflammatory response or necrosis in any of the animals, and this is concordant with studies that aimed to assess the biocompatibility of α-TCP cement (39,40) . Another possible explanation for the absence of inflammation or bone necrosis is that saline solution was used to constantly irrigate the surgical field while the defects were being created, and that both the cement and the surgical materials used in all the procedures had been sterilized.…”
Section: Discussionsupporting
confidence: 85%
“…Pre-operatively, rats were anesthetized with tiletamine zolazepam (Virbac Korea, Seoul, Korea) and xylazine HCl (Bayer Korea, Kyungkido, Korea). Rats were divided into five groups: Control (defect alone), Vetbond (3M, St. Paul, USA), CMP, HA, and HA-col. For evaluation of osteoconductive potency, a 2-mm diameter cortical bone defect was created in the diaphysis of the femur using a dental drill [33] , followed by the implantation of each of the prepared bioceramics including CMP, HA, and HA-col in the lesion. Defects were carefully and sufficiently lavaged using 0.9% saline.…”
Section: Methodsmentioning
confidence: 99%